Mixed- Precision Algorithm in Electromagnetic Finite Element Method - Zhi-ming, Li; Hao-xiang, Wu; Sheng, Zuo; Xi, Chen (2023 International Applied Computational Electromagnetics Society Symposium (ACES-China), 2023)
Single-precision algorithms are known to offer superior computational efficiency compared to double-precision algorithms. However, achieving the same level of computational accuracy as double-precision algorithms in single-precision arithmetic can be challenging. Mixed-precision algorithms have emerged as a promising solution to this problem. In this study, we employ a mixed-precision algorithm to solve the matrix equation Ax=b generated by the electromagnetic finite element method. Specifically, single-precision arithmetic is utilized in the matrix factorization phase, whereas double-precision arithmetic is applied in the residual calculation and iterative refinement phase. Our experimental results demonstrate that the mixed-precision algorithm achieves computational efficiency that is approximately 1.5 times higher than that of the double-precision algorithm, and occupies 40% less memory. Additionally, the computational accuracy of the mixed-precision algorithm is found to meet the requirements of double-precision arithmetic.